Analysis of the Influence of Convection Heat Transfer in Circular Tubes on Ships in a Polar Environment - Dongwei Yu; Dayong Zhang; Lin Wu; Xiangyi Kong; Qianjin Yue (Atmosphere, 2022)
Electric heat tracing is the main measure for cold protection of the polar transfer coefficient in marine engineering equipment, but thermal equilibrium is the key problem this technology faces. In this paper, the circular tube was the research object. We studied the influence of convective heat transfer by Fluent software and experiments with a wind speed of 0–40 m/s and temperature of −40–0 °C by constant heat flux heating. The results show that the convective heat transfer increases with increased wind speed and decreased temperature. When the temperature is below −30 °C, the effect of temperature is increased; when the wind speed is greater than 25 m/s and the temperature is lower than −20 °C, the effect of temperature on the convective heat transfer coefficient of the circular tube increases. Based on the simulation data, we established a prediction model, and the rationality of the prediction model was verified by tests. The model provides reference for the design of electric heat tracing of circular tubes on polar ships.